2016
DOI: 10.1136/bjsports-2015-095666
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact study: neuromuscular training reduces the burden of injuries and costs compared to standard warm-up in youth soccer

Abstract: Implementation of an NMT prevention programme in youth soccer is effective in reducing the burden of injury and leads to considerable reduction in costs. These findings inform practice and policy supporting the implementation of NMT prevention strategies in youth soccer nationally and internationally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 23 publications
0
54
1
Order By: Relevance
“…Our injury-severity results differed from findings 12,26 in youth players. Although we recorded more moderate injuries (35.3%), Peterson et al 27 reported milder (52%) and less severe (15%) injuries in European soccer players aged 9 to 19 years.…”
Section: Discussioncontrasting
confidence: 99%
“…Our injury-severity results differed from findings 12,26 in youth players. Although we recorded more moderate injuries (35.3%), Peterson et al 27 reported milder (52%) and less severe (15%) injuries in European soccer players aged 9 to 19 years.…”
Section: Discussioncontrasting
confidence: 99%
“…More specifically, the FIFA 11+ prevention programme was shown to have a substantial injury-preventing effect by reducing football injuries by 39%, whereas a preventive effect from the FIFA 11 prevention programme alone could not be documented. Reducing injuries to this extent by using an exercise-based prevention programme has, furthermore, been shown to reduce injury-related costs in football by more than 40% 36 51…”
Section: Discussionmentioning
confidence: 99%
“…Literature regarding the cost-effectiveness of injury prevention interventions in soccer is limited. A reduction of 43% was reported in healthcare costs in the training group that underwent an NMT warm-up similar to the 11+ program with additional use of a wobble-board, when compared to a standard practice control group [55]. Similarly, the "11+ Kids" program showed a 51% reduction in healthcare costs when compared with a regular warm-up [56].…”
Section: Cost-effectiveness Of Interventionsmentioning
confidence: 92%